Infusion pump flow rates in central venous catheters: Thrombus reflux and aspiration clot. - Martinez,Jose Manuel (2021)
Abstract Aggressive infusion pump flow rates can lead to central venous catheter (CVC) occlusion resulting from thrombus reflux into the CVC lumen. Methods: A single-center prospective comparative study was performed, including all consecutive cases of occlusion events in hematology oncology patients using a CVC (Hickman® nº7) since August 2018 to September 2019 (Phase 1), and October 2019 to September 2020 (Phase 2) at the Onco-Hematology Department of the Portuguese Institute of Oncology (Porto). Two phases were described: Phase 1: Observational period using a platinum-based regime (DHAP) undergoing continuous infusion pump rate ≥ 200 mL/hr. Phase 2: Intervention period using a platinum-based regime (DHAP) undergoing continuous infusion pump rate ≤ 200 mL/hr. Results: Overall, 39 DHAP regimens were reported with a total number of 43 occlusions identified in the study period (phase 1, n=28 vs phase 2, n=15). Occlusion risk associated with the infusion pump rates between phases was higher in phase 1 (phase 1, n=11 vs phase 2, n=3, RR 3.313 [1.010 to 13.863], ≤0.05). When aspiration clot (n=5) was identified, CVC always was removed. No aspiration clot was observed in phase 2. Conclusion: Aggressive infusion pump flow rates can increase occlusion risk resulting from thrombus reflux into the CVC lumen and aspiration clot.